2009
DOI: 10.1007/s00270-009-9749-6
|View full text |Cite
|
Sign up to set email alerts
|

The AMPLATZER Vascular Plug 4: Preliminary Experience

Abstract: The purpose of this communication is to describe our preliminary experience with the Amplatzer Vascular Plug 4 (AVP 4) in peripheral vascular embolization. The AVP 4 was used for peripheral vascular embolization in five patients with renal pseudoaneurysm (n = 2), postsurgical peritoneal bleeding (n = 1), posttraumatic gluteal hemorrhage (n = 1), and intercostal pseudoaneurysm (n = 1). Occlusion time was recorded. Patients were followed up clinically and by imaging for 1 month after the procedure. All treated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 9 publications
1
28
1
Order By: Relevance
“…Therefore, in most cases, a single plug is sufficient for complete vessel occlusion. The use of one plug results in a significant reduction in the number of procedural steps, which in turn results in lower radiation exposure, reduced procedure time, and lower complication rates (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in most cases, a single plug is sufficient for complete vessel occlusion. The use of one plug results in a significant reduction in the number of procedural steps, which in turn results in lower radiation exposure, reduced procedure time, and lower complication rates (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…The English literature describes the utility of the AVP 4 in renal pseudoaneurysm, postsurgical peritoneal bleeding, posttraumatic gluteal hemorrhage, intercostal pseudoaneurysm, and arteriovenous fistula after in situ saphenous vein bypass grafts (1)(2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on experience in peripheral and cardiac interventions, vessel occlusion devices have been used for cranial vessels [16,17]. Studies have shown effective embolization with the Amplatzer Vascular Plug used in conjunction with coils for the treatment of cavernous carotid aneurysm and pulmonary arteriovenous fistulas [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the AMPLATZER Vascular Plug (AVP) (St. Jude Medical, Inc, St. Paul, Minnesota) compared with pushable coils has shown similar high technical success rates with low complication rates in the literature (3)(4)(5)(6). The ability to recapture and reposition the device provides an added benefit of the AVP over pushable coils.…”
mentioning
confidence: 95%